Pengembangan Modul Ajar Berbasis Model Pembelajaran Discovery Learning dalam Mengembangkan Profil Pelajar Pancasila Kelas IV SD - A Andriyanto; Retno Utaminingsih; Ana Fitrotun Nisa (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2023)
The purpose of this study was to describe the characteristics of teaching modules based on discovery learning models, describe the feasibility of teaching modules and describe the effectiveness of teaching modules in developing Pancasila student profiles. This research is research and development involves adapting and modifying the Borg and Gall procedure into eight steps. Data collection techniques include observation, interviews, questionnaires, and documentation. Data analysis techniques using descriptive statistical analysis. The teaching modules developed have characteristics in terms of interesting content and design, integration with the discovery learning model, and the attitude profile of Pancasila students. The results of the material expert validation obtained a percentage of 100%, the media expert validation obtained a percentage of 97,5%, and the class IV A teacher validation obtained a percentage of 98,75%. The results of the students' responses obtained a percentage of 96,8%. The results of the effectiveness of the teaching modules showed an increase in the overall dimensions of the Pancasila student profile of 33,17%. Based on these results, the teaching module based on the discovery learning model is declared to have the feasibility and effectiveness necessary to develop a Pancasila student profile for fourth grade elementary school students.